Urban and rural inequality in knowledge, attitude and practice on haze in Klang Valley - Nathanael Vethanayagam James.
Introduction: Haze occurs during the southwest monsoon season because low level winds over Malaysia are generally south-westerly and the weather is generally dry. Fine particulate matter which primarily derived from direct emission from combustion processes has most concern towards the health effect due to its toxicological and physiological considerations which suggest that the fine particles may play the largest role in affecting human health. As awareness of the source and dangers of smoke haze spread. Malaysian government increasingly came under pressure from the public and civil society at the national, state, and district level to address the haze issue. The knowledge, attitude and practice inequalities of urban and rural community could be a barrier in promoting awareness on haze. Objectives: To determine the urban and rural inequality in knowledge, attitude and practice on Haze. Methodology: The sample population for this study are the urban and rural residents of Klang Valley.The sample size was 400 from both urban and rural community. For this cross-sectional study, the purposes is to determine the inequalities in knowledge attitude and practice on haze. The Sampling Frame was obtained from the Local Government Department of Klang Valley. The population was then selected based on their inclusive criteria. The study instrument used is a standardized questionnaire. The questionnaire was constructed and are pretested. The questionnaires will then be distributed to the urban and rural population of the Klang Valley. The questionnaire consist of two sections that are part A and part B. The section A functions to collect the sociodemographic information o f the participants. While the section B is constructed to collect the overall knowledge. attitude and practice of a selected population. Result and Discussion: There was a difference in knowledge between urban and rural community (p<0.05). There was a difference in practice between urban and rural community (p<0.05).There was also an association between attitude and practice on haze (p<0.05). Conclusion: Both the urban and rural community had moderate level of knowledge, attitude and practice towards haze. The urban and rural community also had difference in terms of knowledge, attitude, and practice towards haze.